Reassessment of the extinction risk of five species of the genus Polianthes L. (Agavaceae) - Feria-Arroyo, Teresa Patricia; Solano, Eloy; García-Mendoza, Abisaí (Instituto de Ecología, A.C., 2010)
We reassessed the extinction risk of the species Polianthes densiflora, P. howardii, P. longiflora, P. palustris and P. platyphylla by applying the MER (method of evaluation of extinction risk of wild species for Mexico). These species are listed as rare by the International Union for Conservation of Nature (IUCN) and are considered to be in the category of special protection according to Mexican regulation. MER criterion A (geographic distribution) was assessed with three methods: area of occupancy, extent of ocurrence, and species distribution models. Criteria B (habitat conditions) and D (impact of human activity) were examined by superimposing the human footprint map of Sanderson et al., where values range from 0 to 100. In this map, 0-10 denote pristine areas and 100 indicates that the habitat has been completely transformed. Criterion C (intrinsic biological vulnerability) was assigned based on the geophytic nature of the species. According to our findings, Polianthes densiflora and P. longiflora are in danger of extinction, while P. howardii and P. platyphylla are endangered and P. palustris is likely extinct. None of the five species concerned occur in any Natural Protected Area. We propose in situ and ex situ strategies to maintain these species as well as the development of programs of sustainable use for Polianthes longiflora and P. platyphylla. These species could be cultivated and domesticated by means of vegetative propagation.